O figurino na narrativa dos filmes de Guel Arraes: O Auto da Compadecida (2000) e O Bem Amado (2010) - Souza, Carla Patrícia Oliveira de (2015)
This research focuses on the course of Guel Arraes, moviemaker, and picks two movies for analysis: O Auto da Compadecida (2000) and O Bem Amado (2010), as well as their costumes. The focus on the costume is based on Semiology and aims to decode the meanings that stem out of the clothes. Three of the movies characters will have their costumes analyzed based on Roland Barthes’ theory, mainly considering semiology elements (language and speech), (significant and meaning) and (system and syntagma). The influence of the Armorial movement into the movie O Auto da Compadecida and the Kitsch aesthetic in O Bem Amado deserve consideration, aside from the study on costumes function within narrative, supported by Roland Barthes’ structural analysis of the narrative. We sought to highlight the balance between characters’ lines and the image of the costumes in the movies. Adding to the study on how costumes strongly accounts to narrative, we observed characteristic traits of director and scriptwriter Guel Arraes present in his works, which are the northeastern man identity, a presentation of the Northeast and popular comedy. We believe that his choices when creating and his life influences are not separate from one another. Our research was movie-appraisal centered and had a thorough investigation all over language. The main considerations are supported by the following theories: Barthes (2007), Figueirôa and Fechine (2008), Moles (2001), Stuart Hall (2005) and Mikhail Bakhtin (2013).